Faktor-Faktor yang Mempengaruhi Islamic Governance Perbankan Syariah di Indonesia - Rio Trisasmita (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aims to analyze the influence of the existence of Sharia Supervisory Board, composition of the Sharia Supervisory Board, Board of Commissioners, Composition of the Board of Commissioners, Audit Committee, Profitability and Liquidity to the Islamic Governance either partially or simultaneously. The data used is secondary data with purposive sampling and selected as many as 10 samples of Sharia Bank. Hypothesis testing in this research by using logistic regression model. The results of this study indicate that the existence of Sharia Supervisory Board (DPS) has a significant influence on Islamic Governance. The Board of Commissioners has no influence on Islamic Governance. The composition of the Board of Independent Commissioners has no influence on Islamic Goverance. The Audit Committee has no influence on the Islamic Governance. Furthermore, profitability and liquidity have no effect on Islamic governance.